Mechanism of Ferroptosis and Its Relationships With Other Types of Programmed Cell Death: Insights for Potential Interventions After Intracerebral Hemorrhage - Zhou, Sheng-Yu; Cui, Guo-Zhen; Yan, Xiu-Li; Wang, Xu; Qu, Yang; Guo, Zhen-Ni; Jin, Hang (Frontiers in Neuroscience, 2020)
Intracerebral hemorrhage (ICH) is a fatal cerebrovascular disease with high morbidity and mortality, for which no effective therapies are currently available. Brain tissue damage caused by ICH is mediated by a newly identified form of non-apoptotic programmed cell death, called ferroptosis. Ferroptosis is characterized by the iron-induced accumulation of lipid reactive oxygen species (ROS), leading to intracellular oxidative stress. Lipid ROS cause damage to nucleic acids, proteins, and cell membranes, eventually resulting in ferroptosis. Numerous biological processes are involved in ferroptosis, including iron metabolism, lipid peroxidation, and glutathione biosynthesis; therefore, iron chelators, lipophilic antioxidants, and other specific inhibitors can suppress ferroptosis, suggesting that these modulators are beneficial for treating brain injury due to ICH. Accumulating evidence indicates that ferroptosis differs from other types of programmed cell death, such as necroptosis, apoptosis, oxytosis, and pyroptosis, in terms of ultrastructural characteristics, signaling pathways, and outcomes. Although several studies have emphasized the importance of ferroptosis due to ICH, the detailed mechanism underlying ferroptosis remains unclear. This review summarizes the available evidence on the mechanism underlying ferroptosis and its relationship with other types of cell death, with the aim to identify therapeutic targets and potential interventions for ICH.